Hormonal and Cytokine Imbalances Promote a Proinflammatory Profile in Institutionalized Elderly - Sfredo, Arce dos Santos; Silva, Marcondes Alves Barbosa da; Melo, Laura Valdiane Luz; França, Danielle Cristina Honorio [UNESP]; Dantas, Gabriel Lopes; Santos, Wagner Batista dos; Fagundes-Triches, Danny Laura Gomes; Marchi, Patrícia Gelli Feres de; Honorio-França, Adenilda Cristina; França, Eduardo Luzía (MDPI, 2025)
Background: Aging is accompanied by chronic low-grade inflammation (inflammaging) and neuroendocrine–immune imbalance. This study evaluated blood concentrations of cortisol, melatonin, and Th1/Th2/Th17 cytokines in elderly individuals. Methods: A cross-sectional study was conducted, including institutionalized elderly individuals (n = 32) and elderly individuals living with family members (n = 29). Blood samples were collected between 8:00 and 10:00 a.m. for cytokine quantification (IL-2, IL-4, IL-6, IL-10, IL-17, TNF-α, IFN-γ) by flow cytometry and for cortisol and melatonin measurement by ELISA, ensuring accurate interpretation while considering their circadian variations. Results: Institutionalized individuals showed higher IL-6 (p = 0.0261) and IFN-γ (p = 0.0065), and lower IL-2 (p = 0.0006), IL-4 (p = 0.0043), IL-17 (p = 0.0025), and TNF-α (p = 0.0243). Blood cortisol (p = 0.0309) and melatonin (p = 0.0407) were also elevated. Cortisol correlated negatively with IL-2 (r = −0.5986, p = 0.0397) and IL-6 (r = −0.6135, p = 0.0338). Conclusions: Institutionalization is associated with elevated blood hormone levels and an imbalanced cytokine pattern, indicating disruption of the neuroendocrine–immune network. These alterations align with the concept of inflammaging and highlight the impact of the living environment on immune–endocrine regulation in older adults.